Automated chromosome damage analysis to investigate thresholds for genotoxic agents. - Katja Brusehafer (2013)
Genotoxicology involves the assessment of a substance’s ability to induce DNA damage after exposure to humans. DNA damage is an underlying cause of mutations that are likely to initiate carcinogenesis. Furthermore, the investigation of low dose responses in genotoxicology testing helps to improve health risk assessment by establishing whether DNA reactive compounds follow linear or non-linear (thresholded) dose response relationships.The current assumption for direct acting genotoxins is that the relationship between exposure to genotoxic chemicals, DNA damage formation and the induction of mutagenic changes is linear. However, it is known that mutations are not produced directly by DNA adducts as DNA repair activity limits the proportion of adducts processed into mutations. It is therefore possible, that no observed effect levels (NOEL) may exist for some genotoxins.The main aim of this thesis was to improve in vitro genotoxicity testing by assessing the low dose response relationships for the genotoxic agents mitomycin-C (MMC), 4-nitroquinoline 1-oxide (4NQO) and cytosine arabinoside (araC). Furthermore, the automated micronucleus slide scoring system Metafer was validated and used for these studies.In addition, the mechanism of action of each test component was further investigated by follow up experiments to gain a better understanding of the processes involved in this type of damage.The in vitro micronucleus assay for the detection of chromosomal damage revealed nonlinear dose response relationships following low dose exposure of MMC and araC, while 4NQO revealed a weak clastogenic potential. The semi-automated scoring protocol for the Metafer-System proved to be a rapid and accurate system for scoring micronuclei.DNA repair plays most likely a major role in these non-linear responses by removing genetic damage induced at low levels. Furthermore, p53 was shown to be involved in the DNA damage response in human lymphoblastoid cells, through cell cycle delay and the induction of apoptosis.In addition, this work confirmed that a proper dosing regime, accurate toxicity measurements and the appropriate choice of cell type are cmcial criteria for defining the dose response relationships and the induction of genotoxicity and cytotoxicity.